Evaluation of nucleotide MALDI-TOF-MS for the identification of Mycobacterium species - Zhu, Yelei; Liu, Zhengwei; Peng, Lina; Liu, Bin; Wu, Kunyang; Zhang, Mingwu; Wang, Xiaomeng; Pan, Junhang (Frontiers in Cellular and Infection Microbiology, 2024)
Background The accurate identification of the Mycobacterium tuberculosis complex (MTBC) and different nontuberculous mycobacteria (NTM) species is crucial for the timely diagnosis of NTM infections and for reducing poor prognoses. Nucleotide matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) has been extensively used for microbial identification with high accuracy and throughput. However, its efficacy for Mycobacterium species identification has been less studied. The objective of this study was to evaluate the performance of nucleotide MALDI-TOF-MS for Mycobacterium species identification. Methods A total of 933 clinical Mycobacterium isolates were preliminarily identified as NTM by the MPB64 test. These isolates were identified by nucleotide MALDI-TOF-MS and Sanger sequencing. The performance of nucleotide MALDI-TOF MS for identifying various Mycobacterium species was analyzed based on Sanger sequencing as the gold standard. Results The total correct detection rate of all 933 clinical Mycobacterium isolates using nucleotide MALDI-TOF-MS was 91.64% (855/933), and mixed infections were detected in 18.65% (174/933) of the samples. The correct detection rates for Mycobacterium intracellulare, Mycobacterium abscessus, Mycobacterium kansasii, Mycobacterium avium, MTBC, Mycobacterium gordonae, and Mycobacterium massiliense were 99.32% (585/589), 100% (86/86), 98.46% (64/65), 94.59% (35/37), 100.00% (34/34), 95.65% (22/23), and 100% (19/19), respectively. For the identification of the MTBC, M. intracellulare, M. abscessus, M. kansasii, M. avium, M. gordonae, and M. massiliense, nucleotide MALDI-TOF-MS and Sanger sequencing results were in good agreement (k > 0.7). Conclusion In conclusion, nucleotide MALDI-TOF-MS is a promising approach for identifying MTBC and the most common clinical NTM species.